Analysis of Rabbit fillet business with the business model canvas approach at Azhar Farm - Siti Azizah; Hafidz Budi Handoko (Faculty of Animal Science, Universitas Brawijaya, 2020)
The Azhar Farm rabbit fillet business is currently facing various obstacles to maintain sustainability and expand the product marketing area, the Azhar Farm company is demanded to be able to improve performance by improving its previous business model.This research was conducted to find a general description of the business, the business model of canvas that has been used, and create improvement recommendations for business models of the rabbit fillet business at Azhar Farm. This type of research is descriptive. The Business Model Canvas uses a qualitative approach, while the SWOT uses a quantitative approach with data collection conducted for two and a half months from January to March 2020.This research is focused on the level of renewal of information obtained from the real situation. It provides recommendations for business models improvement with the Business Model Canvas tool by looking at Azhar Farm through the nine elements of BMC. The SWOT analysis results show that the value of the axis (X) of 0.68 and the value of the axis (Y) of 0.97 reflect a positive state and are in quadrant I with the strategy that must be implemented is aggressive.In the rabbit fillet,Azhar Farm also needs to make improvements to the nine elements of BMC to be able to compete and expand the market and maintain stability in the business.